PENERAPAN MEDIA PEMBELAJARAN WONDERSHARE FILMORA PADA PEMBELAJARAN MATEMATIKA - Alfitra Zoelva Annida Yusuf; Rahma Faelasofi; Siti Rahayu (IKIP Siliwangi, 2022)
The purpose of the study was to determine whether there was a difference between the average mathematics learning outcomes of students using the online learning model assisted by Wondershare Filmora learning media and the average mathematics learning outcomes of students using the online learning model without the aid of Wondershare Filmora learning media. This type of research is a comparative quantitative research. The population in this study were students of class IX SMP Negeri 1 Kalirejo. Data analysis was processed by two-party t-test and one-party t-test with the prerequisites for normality and homogeneity tests. The results showed that there was a difference in the average mathematics learning outcomes of students who used the online learning model assisted by Wondershare Filmora learning media and the average mathematics learning outcomes of students who used the online learning model without the aid of Wondershare Filmora learning media. One-sided t-test shows that the average mathematics learning outcomes of students who use the online learning model assisted by the Wondershare Filmora learning media are better than the average mathematics learning outcomes of students who use the online learning model without the aid of Wondershare Filmora learning media.